2016
DOI: 10.1007/s11042-016-3845-9
|View full text |Cite
|
Sign up to set email alerts
|

Academic methods for usability evaluation of serious games: a systematic review

Abstract: In the last years, there has been an increasing interest in the design of video games as a tool for education, training, health promotion, socialization, etc. Usability, which is a key factor in any video game, becomes even more important in these so-called Bserious games^, where the users' special characteristics should be considered, and the game efficacy depends on the users' adherence and engagement. However, evaluation of the usability of this kind of games requires a redefinition of techniques, methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 213 publications
0
21
0
Order By: Relevance
“…The SUS questionnaire consists of ten statements, evaluated with a Likert scale, which have to be evaluated immediately after the use of the system, even before the debriefings or discussion [41]. As shown in the surveys [44,45], SUS is the most commonly used standard questionnaire for measuring the usability of the serious game approaches.…”
Section: Impact On the Perceived Usability Of The Erp Systemmentioning
confidence: 99%
“…The SUS questionnaire consists of ten statements, evaluated with a Likert scale, which have to be evaluated immediately after the use of the system, even before the debriefings or discussion [41]. As shown in the surveys [44,45], SUS is the most commonly used standard questionnaire for measuring the usability of the serious game approaches.…”
Section: Impact On the Perceived Usability Of The Erp Systemmentioning
confidence: 99%
“…These user tests were concentrated within the period of 2002 and 2016 where the majority of the usability tests (83%) were performed with healthy people and the others (17%) involved patients or a combination of users with differing abilities [13]. Demographic data collected from the articles conducting these tests showed that 62% of them tested young participants, mostly university students with an average age of 30 years [12].…”
Section: Literaturementioning
confidence: 99%
“…These previous reviews [9][10][11][12][13] provided a starting point and a reference for structuring this study. Through the selection and classification of the articles, the information was analysed, in order to gain an overview and summary of the research findings.…”
Section: Literaturementioning
confidence: 99%
“…In the study participated 26 patients undergoing treatment for GD, giving high scores in effectiveness, efficiency, and satisfaction with the use of the tablet-based serious game e-Estesia (according to the SUS; Brooke, 1996). This is one of the few studies conducted in order to evaluate usability of a serious game in clinical population (Yáñez-Gómez et al, 2017). The app performed comparatively well in all groups.…”
Section: Discussionmentioning
confidence: 90%